At what level of corruption does economic growth decrease?. Issue 4 (4th March 2020) - Trabelsi, Mohamed Ali; Trabelsi, Hédi
Abstract : Purpose: The purpose of this study is to examine the impact of corruption on economic growth by testing the hypothesis that the relationship between these two variables is nonlinear and by assessing the veracity of the assumption that corruption is always detrimental to economic growth. Several cross-country studies have treated this question but the findings are not universally robust. Design/methodology/approach: In this paper, a panel data analysis has been used to examine 88 countries over the 1984-2011 period. A cross-sectional framework is used in which growth rate and the International Country Risk Guide (ICRG) index are observed only once for each country. Findings: The findings indicate that beyond an optimal threshold, both high and low corruption levels can decrease economic growth. Under this optimal threshold, a moderate level of corruption, defined by the point of reversal of the curve of the marginal corruption effect on growth, could have advantages for economic growth. Originality/value: This paper shows that the threshold would be a corruption level between 2.5 and 3, which represents the "acceptable corruption level". This result is conforming to one of the ten principles of economics: "Rational people think at the marginal change". This threshold represents the point where the marginal benefits of corruption are equal to marginal costs incurred by corruption. Conversely, lack of corruption may be a mechanism that slows down growth.